Molecular targets modulated by fangchinoline in tumor cells and preclinical models - Mérarchi, M.; Sethi, G.; Fan, L.; Mishra, S.; Arfuso, Frank; Ahn, K. (M D P I AG, 2018)
© 2018 MDPI AG. All rights reserved. Despite tremendous progress made during the last few decades in the treatment options for cancer, compounds isolated from Mother Nature remain the mainstay for therapy of various malignancies. Fangchinoline, initially isolated from the dried root of Stephaniae tetrandrine, has been found to exhibit diverse pharmacological effects including significant anticancer activities both in tumor cell lines and selected preclinical models. This alkaloid appears to act by modulating the activation of various important oncogenic molecules involved in tumorigenesis leading to a significant decrease in aberrant proliferation, survival and metastasis of tumor cells. This mini-review briefly describes the potential effects of fangchinoline on important hallmarks of cancer and highlights the molecular targets modulated by this alkaloid in various tumor cell lines and preclinical models.